WORKSHOP AND ASSISTANCE: ENHANCEMENT OF ELEMENTARY SCHOOL TEACHERS ON WRITING RESEARCH PAPER - Muhammad Iqbal Ripo Putra; Aunurrahman Aunurrahman; Desi Sri Astuti; Senny Wiyanti; Dedi Irwan (LPPM IKIP PGRI Pontianak, 2021)
This workshop's primary goal is to provide professional elementary school teachers writing scientific papers for their professional development. Operationally, the objectives of the activity are 1) skilled teachers who are ready to carry out the socialization of various types of teacher professional development; 2) talented teachers to be able to develop professions, especially in writing classroom action research (CAR) papers; 3) Improved teachers in compiling research reports and scientific journal articles; 4) Compilation of research reports on CAR activities written by teachers. To achieve this goal, training, workshop, and mentoring methods are used. At the end of this program, the following results were obtained: 1) A total of 25 elementary teachers attended the training activity as a whole for 26 lesson hours; 2) There was four times assistance in planning, implementing, and writing CAR reports; 3) There are 25 CAR reports that each participant has provided with the assisting team's guidance and direction; 4) The two best articles are ready to be published in periodicals published by institutions. This activity is an extension of socializing various professional development activities to teachers in the field, especially in scientific papers from classroom action research in the future.